2018
DOI: 10.1111/jen.12574
|View full text |Cite
|
Sign up to set email alerts
|

Effects of glufosinate‐ammonium herbicide and pod sealant on spider Pardosa agrestis

Abstract: Herbicides based upon glufosinate‐ammonium (GLA) are among the world's most widely used. They also are applied on the most prominent oil crops as desiccants in combination with pod sealants to prevent pod shatter and seed loss close to harvest. Even though these crops occupy a significant part of the world's agroecosystems, the effects of GLA herbicides on non‐target arthropods, and in particular natural enemies of pests, have been studied very rarely, and such effects of pod sealants have never been studied. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…In a recent study, Lavelle et al (2022) showed that the worldwide abundance of soil macroinvertebrate communities drastically decreases in conventional cropping systems. In our study, the increase in macrofauna abundance within the ecological friendly cropping systems may be due to moderate levels of pesticides, herbicides and mineral fertilizer applications (Sánchez-Moreno et al, 2009;Niedobová et al 2019;Loranger-Merciris et al, 2022;Zulu et al 2022).…”
Section: Cropping Systems and Soil Healthmentioning
confidence: 62%
“…In a recent study, Lavelle et al (2022) showed that the worldwide abundance of soil macroinvertebrate communities drastically decreases in conventional cropping systems. In our study, the increase in macrofauna abundance within the ecological friendly cropping systems may be due to moderate levels of pesticides, herbicides and mineral fertilizer applications (Sánchez-Moreno et al, 2009;Niedobová et al 2019;Loranger-Merciris et al, 2022;Zulu et al 2022).…”
Section: Cropping Systems and Soil Healthmentioning
confidence: 62%
“…Godfrey and Rypstra (2018; showed, that different concentrations of the herbicide atrazine may significantly decrease the probability of egg-sac production of wolf spiders (Lycosidae) and may act as stressor for individuals. No changes were detected in predatory behaviour of lycosid spiders under exposure to the herbicide Roundup Biaktiv (Michalková and Pekár, 2009) or Roundup klasik Pro (Niedobová et al, 2019a). On the other side, solution of the glyphosate-based herbicide Glifoglex affected almost all aspects of life of orb-weaver spider Alpaida veniliae Keyserling 1865, from web building and fertility to prey consumption (Benamú et al, 2010).…”
Section: Resultsmentioning
confidence: 98%
“…These studies have measured locomotion (Wrinn et (Wrinn et al 2012). These studies varied widely in exposure method and duration including a single topical application with (Evans et al 2010) and without spider anaesthetization (Niedobová et al 2018, Hof et al 1995. Other exposure methods included brief contact with a recently sprayed paper surface (e.g.…”
Section: ; Schütte Et Al 2017)mentioning
confidence: 99%